The Urgency of Islamic Religious Education in the Formation of Muslim Personality Concepts - Sifa Anissatuzzahro; Esi Hairani (Universitas Muhammadiyah Enrekang, 2025)
Islamic religious education plays a central role in shaping a strong and integrated concept of Muslim personality. This paper explores the urgent importance of Islamic religious education in the process of forming personality concepts rooted in Islamic values. Through literature analysis and qualitative approaches, we investigate how Islamic religious education provides a solid foundation for the development of character, morality, ethics, and attitudes in accordance with Islamic teachings. The significant contribution of Islamic religious education to the development of Muslim personalities with integrity impacts not only at the individual level but also at the social and community levels as a whole. This research also highlights the challenges and opportunities in implementing effective Islamic religious education in the contemporary era filled with global dynamics. By understanding the urgency of Islamic religious education, we can strengthen our commitment to shaping Muslim personalities grounded in the values of truth, justice, compassion, and high morality, thus enabling them to positively contribute to building a harmonious and civilized society.